Evaluation of an organic diet intervention to reduce pesticide exposure: a repeated measures cross-over study among rural and urban communities in Selangor, Malaysia - Vivien How; Maisarah Nasution Waras; Jamilatul Wahidah Jamal Rodzi; Nurul Afina Ahmad Zamani; Hafizah Rukman (Environmental Research Communications)
Introduction . Organophosphate (OP) pesticides are widely used in agriculture, resulting in dietary pesticide exposure through conventionally grown foods. While organic diets are often recommended to reduce pesticide burden, the effectiveness of such interventions and the influence of local environmental factors and metabolic differences remain underexplored in mixed urban–rural settings. This study investigated the impact of a short-term organic diet intervention on urinary OP metabolite concentrations among rural and urban adults and children in Selangor, Malaysia, and assessed the rebound effect after returning to a conventional diet. Method . Seventeen families (9 rural, 8 urban) participated in a 16-day cross-over intervention, consisting of a baseline conventional diet phase (4 days), an organic diet phase (7 days), and a post-intervention conventional diet phase (5 days). Daily first-morning void urine samples were analyzed for four OP metabolites (DMP, DEP, DMTP, DETP). Linear mixed-effects models assessed differences across dietary phases, and daily trends illustrated changes over time. Result . Urinary concentrations of DMP, DEP, and DMTP declined significantly during the organic diet phase compared to baseline (p < 0.05), with the largest reductions observed in children. DETP levels remained relatively stable across phases. Rebound effects were evident for DMP and DMTP when participants resumed a conventional diet, particularly among rural children, reflecting ongoing environmental exposure and age-related differences in metabolic clearance. Urban adults showed the most consistent reduction, while rural families exhibited greater variability due to overlapping dietary and non-dietary pathways. Conclusion . A short-term switch to an organic diet can significantly reduce urinary OP metabolite concentrations, but re-exposure occurs rapidly once conventional foods are reintroduced, especially among children in agricultural settings. These findings highlight the importance of sustained dietary changes, improved pesticide management, and policies that increase access to affordable organic produce. Future research should examine longer-term interventions and integrate health outcome monitoring to support evidence-based pesticide exposure reduction strategies.